Comparative Study Between Outcome of Early and Conventional Catheter Removal After Transurethral Resection of Prostate (Bangladesh Journal of Urology, 2020)
Objectives: To compare the effect of early and conventional catheter removal after TURP.Methods: The cases were selected from the admitted patients with BPH by using simple purposive sampling technique. Sixty (60) cases were included in the study fulfilling selection criteria of the patient and numbered chronologically according to their data and time of operation. Odd numbers of cases were included in group-A (n=30) for early catheter removal within 48 hours and even numbers of cases in group-B (n=30) for conventional catheter removal within 3-5 days.Results: Postoperative hospital stay 47.12 (±7.92) hours in group A and 113.23(±10.8) hours were in group B (p